Game theoretical analysis of the football Inference from English Premier League - Yildirim Beyazit Cicen (Revista Brasileira de Futsal e Futebol)
Football is a prevalent sport in the world. In this study, game-theoretical analysis is used to examine the assumptions of teams competing in the English Premier League and their results. In matches between equal teams, the Nash equilibrium is a draw, whereas in matches between strong and weak teams, the Nash equilibrium is the strong team's defeat. The average of winning the match and the average of goals scored were not high enough, indicating that the teams did not take the field to win. As a result, it's created a goal-oriented proposal in the study's final section. In this proposal, matches will be limited to 60 minutes. The team that scores the third goal will win the game, ending in that minute.